Perancangan dan Pembuatan Web ERP untuk PT Cipta Tekno Mandiri Menggunakan Framework Yii 2 - Taufik Hidayat; Rasyidah (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
PT Cipta Tekno Mandiri is a software house that offers software development services. In the sense of a company whose main product is the development and provision of software or applications. PT Cipta Tekno Mandiri also offers domain and hosting services, as well as programming course services. To assist PT Cipta Tekno Mandiri in sharing information between departments, it is necessary to have an Enterprise Resource Planning (ERP) system that functions to integrate every existing department. Through this system, each department can exchange information with each other. ERP that is made web-based, to speed up the website creation process, a framework is needed. The framework used is Yii 2. Yii is a framework that has amazing performance. The Yii framework makes it easy for programmers to create a web-based application. This ERP was developed using the waterfall method. The waterfall method is a sequential software development method starting from the stages of data collection, design, coding, testing and maintenance.